THE EFFECTS OF COENZYME Q10 MICELLAR SOLUTION AND NANOLIPOSOMES ON SUPEROXIDE DISMUTASE (SOD) ACTIVITY IN CISPLATIN-INDUCED OXIDATIVE STRESS IN RATS - Shikole, Emilija; GJorgoski, Icko; SHalabalija, Dushko; Glavas Dodov, Marija; Trojachanec, Jasmina (SHMSHM - AAMD, 2023)
Introduction: CoenzymeQ10 (CoQ10) is a lipid-soluble antioxidant that plays a key role in the mitochondria respiratory chain in the synthesis of adenosine triphosphate (ATP). It combats the oxidative stress in the body via increasing endogenous cellular defense system represented by superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and glutathione reductase (GR) activity. Cisplatin is an antineoplastic drug used for treatment of various human malignances but because of its cytotoxicity, the therapeutic outcome of this drug is limited. Namely, it causes oxidative stress in the body by reducing the levels for glutathione (GSH), SOD, GpX, CAT and GR. Therefore, the aim of this study was to evaluate the influence of the CoQ10 supplementation (in a form of micellar solution or encapsulated into nanoliposomes) on SOD activity in oxidative stress, induced by the treatment with Cisplatin on rats. Materials and methods: 90 normotensive Wistar rats (250-300 g) were included in this study. The animals were divided in 6 groups, each consisting of 15 rats. Cisplatin (5 mg/kg) and different formulations/combinations with CoQ10 (micellar solution or nanoliposomes dispersion, 10 mg/kg) were administrated i.p. After 12 days, both kidneys were removed for measuring of SOD activity in the tissue. SOD activity was determined by the autoxidation of pyrogallol spectrophotometrically at 420 nm. Statistical analysis was performed using Statistica 7.1 for Windows. Significance was determined at p<0.05 Results: CoQ10 nanoliposome treated group showed significantly increased SOD activity, compared to all other five groups. CoQ10 nanoliposome/Cisplatin treated group showed significantly increased SOD activity compared to the Cisplatin group. Additionally, CoQ10/Cisplatin group showed increased kidney SOD activity, compared to the Cisplatin group. Conclusion: According to these results, CoQ10, as a potent antioxidant and encapsulated into nanoliposomes could be one of the possible solutions to reduce the oxidative stress and nephrotoxicity caused by the cisplatin treatment as a side effect, which is a common reason for reducing or discontinuing therapy.
Keywords: SOD activity; oxidative stress; cisplatin; coenzyme Q10; micellar solution; nanoliposomes